Genetic Responsibility in Germany and Israel Practices of Prenatal Diagnosis - Schües, Christina (Bioethik / Medizinethik, 2022)
Prenatal diagnosis, especially noninvasive prenatal testing (NIPT), has changed the experience of pregnancy, prenatal care and responsibilities in Israel and Germany in different ways. These differences reflect the countries' historical legacies, medico-legal policies, normative and cultural identities. Building on this observation, the contributors of this book present conversations between leading scholars from Israel and Germany based on an empirical bioethical perspective, analyses about the reshaping of 'life' by biomedicine, and philosophical reflections on socio-cultural claims and epistemic horizons of responsibilities. Practices and discussions of reproductive medicine transform the concepts of responsibility and irresponsibility.